Natural Clay yang Dimodifikasi Nikel dan Aplikasi Katalitik Untuk Produksi FAME : Efek Support dan Prekursor Nikel - Admi, Admi; Mustika, Mega; Syukri, Syukri (Universitas Andalas, 2025)
This study was conducted to investigate the use of nickel modified clay as heterogeneous catalyst for the production of fatty acid methyl ester (FAME) from crude palm oil (CPO). The catalyst was prepared by Ni2+- exchanged cation supported on clay under controlled conditions. The results of X-ray Fluorescence analysis (XRF) indicated that Ni2+- exchanged cation modified on support of clay. The results of X-ray Diffraction (XRD) analysis confirmed that support of clay with characteristic of kaolinite mineral. Effect of supports of clay (h-clay and c/h-clay) and effect of nickel precursors (nickel sulfate and nickel nitrate) on the catalytic performance of heterogeneous catalysts in the transesterification reaction of CPO were investigated. The obtained data showed that transesterification processes at oil/methanol ratio of 1 : 6, reaction temperature of 85 oC, catalyst/methanol ratio of 1 : 10, and reaction time of 4 h produced yield of 51,19% FAME, 1,9% FAME, 4,74% FAME, and 47,8% FAME for catalytic performance of h-clay, c/h-clay, h-clay/Ni-Sulfate and h-clay/Ni-Nitrate, respectively. Ni2+- exchanged cation supported on h-clay prepared using two different precursors, nickel nitrate indicating higher catalytic activity than nickel sulfate.